Process Mineralogy Research on the Phosphorus Tailings in Yichang - Yangyang CAO; Yuan TANG; Chengtao TIAN; Xuefeng LIU; Zhili LI; Dongsheng HE (Kuangchan zonghe liyong, 2024)
This is an article in the field of process mineralogy. Systematic process mineralogy study on phosphorus tailings was carried out by using the advanced mineral identification and characterization system (AMICS). The chemical compositions, mineral components, embedded characteristics of minerals, particle size, and the characteristics of liberation degree and the other characteristics were mainly studied. The results show that the gangue minerals are mainly dolomite and quartz. The phosphate mineral is mainly collophane which exists in the form of poor intergrowth. The phosphate mineral is extremely finely disseminated and closely associated with the gangue minerals. This study can provide some guidance for the optimization of phosphate ore dressing and the comprehensive utilization of tailings resources.